Pendekatan Rekonstruksi Sosial dalam Pembelajara Pendidikan Agama Islam di Sekolah Menengah Kejuruan (SMK) Negeri 6 Pontianak - Khairunnisyah Khairunnisyah; Sukino Sukino; Imron Muttaqien (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2020)
This research is based on the learning process of Islamic Religious Education which tends to prioritize the students' abilities in the knowing aspect and the skill aspect (doing), while the most important aspect is the religious aspect which is put aside. So this paper seeks to examine the development of Islamic Religious Education material with a social reconstruction approach, as an offer to overcome the challenges of teachers in shaping students into individuals who always practice the Islamic Education material they have learned. The purpose of this study is to determine how the implementation of the development of Islamic Religious Education materials with a social reconstruction approach. The form of research that is considered suitable is a descriptive study with a qualitative approach with the type of field research or field research. Sources of data in this study were 10 students of SMK Negeri 6 Pontianak and 1 PAI teacher. To collect the data, interview techniques and non-participant direct observation techniques were used. The results of the data analysis show that the contextual and social reconstruction-based learning of Islamic Religious Education is able to create an active and enjoyable learning situation, and produce religious students. Penelitian ini dilatabelakangi oleh proses pembelajaran Pendidikan Agama Islam yang cenderung mengedepankan kemampuan siswa pada aspek pengetahuan (knowing) dan aspek keterampilan (doing), sementara aspek terpenting adalah aspek keberagamaan (being) dikesampingkan. Maka tulisan ini berusaha mengkaji pengembangan materi Pendidikan Agama Islam dengan pendekatan rekonstruksi sosial, sebagai tawaran untuk mengatasi tantangan guru dalam membentuk siswa menjadi pribadi yang senantiasa mengamalkan materi PAI yang telah mereka pelajari. Adapun tujuan dari penelitian ini adalah untuk mengetahui bagaimana implementasi pengembangan materi Pendidikan Agama Islam dengan pendekatan rekonstruksi sosial. Bentuk penelitian yang dianggap cocok adalah studi deskriptif dengan pendekatan kualitatif dengan jenis penelitian lapangan atau field research. Sumber data dalam penelitian ini adalah siswa SMK Negeri 6 Pontianak yang berjumlah 10 orang dan 1 orang guru PAI. Untuk mengumpulkan datanya digunakan teknik wawancara dan teknik observasi langsung non partisipan. Hasil analisis data memperlihatkan bahwa pembelajaran Pendidikan Agama Islam yang kontekstual dan berbasis rekonstruksi sosial mampu menciptakan situasi belajar yang aktif dan menyenangkan, serta menghasilkan siswa yang religius.